2008 32nd Annual IEEE Software Engineering Workshop 2008
DOI: 10.1109/sew.2008.17
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation between External Software Quality and Static Code Analysis

Abstract: Only a few studies exist that try to investigate whether there is a significant correlation between external software quality and the data provided by static code analysis tools. A clarification on this issue could pave the way for more precise prediction models on the probability of defects based on the violation of programming rules. We therefore initiated a study where the defect data of selected versions of the open source development environment "Eclipse SDK" is correlated with the data provided by the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…For practitioners, the most interesting result of this study is that defect density, which we use as a proxy for external software quality, is lower when PMD is included in the buildfile. This is also in line with related research from Plosch et al (2008) who found a positive correlation between defects and the number of ASAT warnings by PMD. Although in our case we are not talking about correlations but differences in reported defects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For practitioners, the most interesting result of this study is that defect density, which we use as a proxy for external software quality, is lower when PMD is included in the buildfile. This is also in line with related research from Plosch et al (2008) who found a positive correlation between defects and the number of ASAT warnings by PMD. Although in our case we are not talking about correlations but differences in reported defects.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, we are primarily interested in general trends regarding ASATs to infer information about the evolution of software quality in our candidate projects. Plosch et al (2008) utilized data collected by (Zimmermann et al 2007) and correlated source code quality metrics and defects with warnings found by different static analysis tools. They used three releases of eclipse and presented correlations for different size, complexity and object oriented source code metrics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Plosch et al [19] studied the correlation between the number of FindBugs and PMD issues, and defects in Eclipse SDK 2.0, 2.1 and 3.0. They found positive correlations for both tools (0.34, 0.25 and 0.30 for PMD, and 0.20, 0.08, 0.20 for FindBugs).…”
Section: A First Research Stream: Looking At Single Asa Issues To Fimentioning
confidence: 99%
“…Due to this manual effort, we want to have a closer look on the impact of ASATs on measurable quality. Previous research regarding the impact on quality can be divided into direct measures which target bug fixing commits, e.g., Vetro et al (2011), Thung et al (2012); Habib and Pradel (2018) and indirect measures which use ASAT warnings as part of predictive models, e.g., Nagappan and Ball (2005), Plosch et al (2008), Rahman et al (2014), Querel and Rigby (2018), Lenarduzzi et al (2020), Trautsch et al (2020b) and Querel and Rigby (2021). Both approaches usually suffer from data validation issues.…”
Section: Introductionmentioning
confidence: 99%